STIMULATING EARLY CHILDHOOD CREATIVITY WITH SIMPLE EXPERIMENTAL METHODS - Martini, Martini; Sitorus, Masganti (Department of Early Childhood Education, Universitas Bina Bangsa Getsempena, 2025)
Creativity is a person’s competence in producing a new breakthrough, both in terms of ideas and tangible works, that has uniqueness compared to old findings. This research is intended to objectively describe the application of experimental methods as a means to stimulate the creativity of young learners at TK IT Nurul Ilmi. The type of research used in this study is field research with a qualitative descriptive approach. Data in this research were collected through three main techniques: observation, semi-structured interviews, and documentation. The subjects of this research are early childhood children aged 5 to 6 years located in the Science Centre at TK IT Nurul Ilmi. This study involved 18 students who were purposively selected, with additional data from two informants, namely the class teacher and the supporting teacher. The results of the analysis are reported in narrative form. The data analysis began with the collection of all data, followed by reduction, presentation, and finally verification. The truth of the data in this research was tested using triangulation techniques, namely by utilising various sources and applying different methods. The types of experimental activities include solar eclipse experiments, colour diffusion experiments, salt evaporation experiments, and secret message experiments. The findings of this study indicate that the use of simple experimental methods as a stimulus for the creativity of early childhood at TK IT Nurul Ilmi can enhance children’s thinking skills, creativity, curiosity, and imagination.